2010
DOI: 10.1111/j.1440-1746.2010.06232.x
|View full text |Cite
|
Sign up to set email alerts
|

Sofalcone, a gastroprotective drug, promotes gastric ulcer healing following eradication therapy for Helicobacter pylori: A randomized controlled comparative trial with cimetidine, an H2‐receptor antagonist

Abstract: Sofalcone promoted gastric ulcer healing during 7 weeks of treatment following 1 week of eradication therapy, and the healing rate was equivalent to that of cimetidine. Symptom disappearance rates were significantly better in the sofalcone group than in the cimetidine group. This may be a useful way of using a gastroprotective drug in the H. pylori era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…We found no significant difference in ulcer healing rates 7 weeks after eradication therapy (PP: 71.9% (23/32) vs 71.0% (22/31), p >0.05). (14) Although this study was of H. pylori positive GU ⩾10 mm in size, similar healing rates were seen with a GP and an H 2 RA.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…We found no significant difference in ulcer healing rates 7 weeks after eradication therapy (PP: 71.9% (23/32) vs 71.0% (22/31), p >0.05). (14) Although this study was of H. pylori positive GU ⩾10 mm in size, similar healing rates were seen with a GP and an H 2 RA.…”
Section: Discussionsupporting
confidence: 65%
“…Both ulcer size (diameter) and depth were considered to be factors that affect healing, but due to difficulties in measuring ulcer depth, we chose ulcer size as the major criterion for classification of lesions in this study as previous reports. (10,13,14) Subjects and treating physicians, but not endoscopists, were informed of the allocated treatment. We explained to subjects the benefits of treatment and the importance of compliance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, two chalcones have been used in clinical practice ( Figure 2 ). Metochalcone ( 3 ) was approved as a choleretic drug [ 2 ], and sofalcone ( 4 ) as an anti-ulcer agent that increases the amount of mucosal prostaglandin, conferring a gastroprotective effect against Helicobacter pylori [ 13 ]. In addition, clinical trials have shown that hesperidin methylchalcone ( 5 , tested for chronic venous lymphatic insufficiency) [ 14 , 15 ], and hesperidin trimethylchalcone ( 6 , evaluated for trunk or branch varicosis) [ 16 ] led to the relieving of symptoms, reached reasonable plasma concentrations, and were well-tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…Cimetidine has been used to treat the patients with H. pylori -reduced erosive gastritis and duodenal ulcers. The results show that betel nut clearance rate in cimetidine group is better than a control group [ 16 , 17 ]. However, the drug has low antibacterial activity [ 18 ] and further work needs to address the problem.…”
Section: Introductionmentioning
confidence: 99%